Prior COVID-19 infection increases degenerated oocytes but does not affect IVF outcomes: a prospective cohort study - Chen, Huijun; Guo, Hongxin; Zhao, Qi; Li, Yuan; Lin, Ge; Kalk, Philipp; Hocher, Berthold; Gong, Fei (Frontiers in Endocrinology, 2025)
BackgroundThe global health crisis of coronavirus disease 2019 (COVID-19) continues to impact people of all age groups worldwide. Recent studies increasingly support that COVID-19 infection may affect reproductive function, causing subfertility and infertility. It is a prospective observational cohort study conducted in the Reproductive and Genetic Hospital of CITIC-Xiangya. 781 women recovered from COVID-19 and 388 uninfected controls undergoing IVF treatment. All participants received standard IVF treatment. Oocyte and embryo quality parameters and pregnancy outcomes were analyzed. Primary outcomes were oocyte and embryo quality, secondary outcomes included clinical pregnancy rates.ResultsThe results show that the COVID-19 recovery group had a higher number of degenerated oocytes compared to controls (0.15 ± 0.40 vs. 0.10 ± 0.33, P=0.035). Regression analysis confirmed this association even after adjusting for confounding factors (Adjusted β: 0.065, 95% CI: 0.006-0.099, P=0.026). However, other parameters of oocyte and embryo quality were comparable between groups. No significant differences were observed in clinical pregnancy rate, implantation rate, early miscarriage rate, ectopic pregnancy rate, or ongoing pregnancy rate. The time interval between COVID-19 recovery and IVF treatment did not significantly affect outcomes.ConclusionOur study indicates that prior COVID-19 infection is associated with a slightly increased risk of degenerated oocytes but does not significantly impact other IVF outcomes or subsequent pregnancy rates. The time interval post-infection does not appear to influence IVF outcomes, suggesting no need to delay treatment following COVID-19 recovery. These findings provide reassurance for women planning IVF after COVID-19 infection.